ANALYSIS OF CAST NET SELECTIVITY ON THE CATCH OF SQUID (UROTEUTHIS CHINENSIS) AT THE NIZAM ZACHMAN OCEAN FISHING PORT JAKARTA - Ardani, Ravena Destia; Dewanti, Lantun Paraditha; Liviawaty, Evi; Ismail, Mochamad Rudyansyah (Departemen PSP IPB, 2025)
The Nizam Zachman Ocean Fishing Port (PPS) in Jakarta is a key fisheries hub with many cast nets and high squid landings. However, overfishing in several Fisheries Management Areas (WPP) requires an evaluation of fishing gear selectivity. This research aims to analyze the size distribution of squid (Uroteuthis chinensis) caught, cast net selectivity, and growth, mortality, and recruitment parameters. Data were analyzed using length-frequency distributions and FISAT II software. Results showed that squid mantle lengths ranged from 15–41 cm, with a modal shift from 18 cm in December 2024 to 24 cm in January 2025. The first-capture length (Lc50%) of 26.90 cm, greater than half the maximum length, suggests that cast nets tend to catch appropriately-sized individuals. The selectivity factor (SF) was 7.06, indicating high selectivity. Growth analysis using the Von Bertalanffy model showed an asymptotic length (L∞) of 41 cm, a growth rate (K) of 1.01/year, and a theoretical zero-length time (t₀) of –0.14. Total mortality was 2.02/year, with natural and fishing mortality at 1,10 and 0,92/year, respectively; exploitation rate (0,45) remained below the optimal 0,5. The recruitment pattern shows the highest peak occurred in June (26.89%). Key words: long frequency histogram, population dynamics, size distribution